PROTOTIPE APLIKASI PENCATATAN DIGITAL UNTUK PENGAJUAN DAN PENGAMBILAN DOKUMEN ADMINISTRASI SIPIL MENGGUNAKAN PENDEKATAN SDLC - Aznawi, Nasrul Mahruf; Limbong, Hans Pran; Setiadi, Muhammad Irham; Armansyah, Armansyah (STKIP PGRI Situbondo, 2025)
Traditional recording process in managing the collection of population administration documents, as applied at the Population and Civil Registration Office (Disdukcapil), faces various challenges. These challenges include errors in the writing of the family card issuance number because the large number of incoming documents during operational hours sometimes causes a decrease in the concentration of officers which causes the writing of the same number on the document, in addition, searching for completed documents is less effective because you have to search for the name of the document owner from the many documents that have entered. This research proposes the development of a prototype digital recording application that aims to improve the efficiency of document management. The system is designed using the prototype model of the System Development Life Cycle (SDLC) framework, which is suitable for iterative and user-focused design. The methodology includes observation of traditional processes, collection of system requirements, design of Use Case diagrams, and user-friendly interface design using Canva. The expected result is an application prototype with a user interface design that has consistency in layout, color, ease of use with a success rate of 85% and the prototype meets the suitability of user needs up to 90%.